Mucin modifies microbial composition and improves metabolic functional potential of a synthetic gut microbial ecosystem - HUMPHREY ANDALO MABWI; Erick V.G. Komba; Kilaza Samson Mwaikono; EMMANUEL, HITAYEZU; MAULIASARI, INTAN RIZKI; Jin Jong Beom; PAN, CHEOL HO; Cha, Kwang Hyun (한국응용생명화학회, 2022)
Microbial dysbiosis in the gut is associated with human diseases, and variations in mucus alter gut microbiota. Therefore, we explored the effects of mucin on the gut microbiota using a community of 19 synthetic gut microbial species. Cultivation of these species in modified Gifu anaerobic medium (GAM) supplemented with mucin before synthetic community assembly facilitated substantial growth of the Bacteroides, Akkermansia, and Clostridium genera. The results of 16S rRNA microbial relative abundance profiling revealed more of the beneficial microbes Collinsella, Bifidobacterium, Ruminococcus, and Lactobacillus. This increased acetate levels in the community cultivated with, rather than without (control), mucin. We identified differences in predicted cell function and metabolism between microbes cultivated in GAM with and without mucin. Mucin not only changed the composition of the gut microbial community, but also modulated metabolic functions, indicating that it could help to modulate microbial changes associated with human diseases.